To simplify the expression 5d + 2(3d), you first distribute the 2 to the terms inside the parentheses, which gives you 5d + 6d. Combining like terms, you add the coefficients of the d-terms together to get 11d. Therefore, the simplified expression is 11d.
7+2n
9d+3
5/ 2 -4/ 5 plus 2 expression can be written in simple form as 37/10.
?
2(3d+7)=5+5d. 6d+14=5+5d 6d+9=5d 9=-1d d=-9 I think that's correct. If it is, ur welcome.
3d + 8d - d - 5 = 10d - 5 = 5*(2d - 1)
7+2n
you just solve. the answer is 5
9d+3
-2+5 Addition is commutative, so you can rewrite this as 5-2 5-2=3
5/ 2 -4/ 5 plus 2 expression can be written in simple form as 37/10.
Combine like terms to give 3n + 2
5/8
Simplify 4x + 3 = 2x + 8 2x = 5 x =2½
is eassy
the answer to this problem is -2x^2y^2
13x+27=3x+32 Reorder 13x-3x=32-27 Simplify 10x=5 Simplify x=5/10 Simplify x=1/2 Answer